2019
DOI: 10.1016/j.energy.2018.12.157
|View full text |Cite
|
Sign up to set email alerts
|

Power performance and dynamic responses of a combined floating vertical axis wind turbine and wave energy converter concept

Abstract: Currently, the development of floating wind turbines and wave energy converters (WECs) is both facing the challenge of high cost-of-energy (CoE). A promising way to reduce the CoE is to employ combined wind and wave energy concepts because they can share the same floating platform, mooring systems, and electrical cables and thus reduce the construction cost. Several combined concepts with floating horizontal axis wind turbines (HAWTs) have been proposed and studied. Compared to floating HAWTs, floating vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…On this basis, Mitra et al [104] modified the STC by integrating spring and dashpot between the spar and torus to improve the sway motion. Cheng et al [105] replaced the horizontal axis WT with a vertical axis WT, and believed that it has a good potential to reduce the LCOE. University of Strathclyde [106] proposed a new offshore floating renewable energy system, called HWNC, which adds two tidal turbines compared to STC.…”
Section: Spar Type 4341 Torusmentioning
confidence: 99%
See 1 more Smart Citation
“…On this basis, Mitra et al [104] modified the STC by integrating spring and dashpot between the spar and torus to improve the sway motion. Cheng et al [105] replaced the horizontal axis WT with a vertical axis WT, and believed that it has a good potential to reduce the LCOE. University of Strathclyde [106] proposed a new offshore floating renewable energy system, called HWNC, which adds two tidal turbines compared to STC.…”
Section: Spar Type 4341 Torusmentioning
confidence: 99%
“…The basic concept of the code is shown in figure 41. Cheng et al [105] achieved NUM analysis of the hybrid system by applying the SIMO-RIFLEX-DMS, whose flowchart is shown in figure 42. OUC developed an in-house overall optimization tool, using FAST as the linking code to connect the external WEC module, like advanced quantitative wave analysis (AQWA) and WEC-Sim.…”
Section: Numerical (Num) Simulationmentioning
confidence: 99%
“…The spar: Spars are cylindrical floating structures which achieve stability through the relative position of the centre of gravity and centre of buoyancy. Most common are the Spar-Torus Combinations (STC) presented in [151][152][153][154][155][156], where a spar type wind turbine is combined with a torus-shaped heaving point absorber added at the water surface. The power performance and dynamic response of this combination are discussed in [153], and it is concluded that using combined wave and wind provides lower-cost power as compared to individual wind or wave technology, but the grid integration effects of adding a WEC on wind turbines needs further research.…”
Section: Combined Platformsmentioning
confidence: 99%
“…The accuracy of this method by comparing the calculated results with the experimental data can meet the needs of applications (Luo et al , 2015). Cheng et al (2019) performed fully coupled simulations under turbulent winds and irregular waves. They conducted this study to evaluate its power performance and assess the additional torus’s impact on the floating’s dynamic behavior.…”
Section: Introductionmentioning
confidence: 99%